Friction Audit and Digital Tax e-Compliance in Cross-Border Religious Travel: The Case of Barokah Travel - Utomo, Raras Dwi Pratiwi Wahyu; Fitriah, Zahra Eka; Handoyo, Dwi; Efendi, Safarel Chiquitita Fayendar; Rahmadhani, Elda Putri; Arien, Rafi Atha Irsyad (Journal of Strategic Behaviour Accounting, 2026)
The growing digitalization of tax systems has transformed how compliance is managed, particularly for cross-border service industries such as religious travel. This study focuses on Barokah Travel, an Indonesian-based umrah and hajj agency operating across Indonesia, Saudi Arabia, and Turkey, which faces significant challenges in tax registration and e-compliance due to multijurisdictional differences. The research aims to map the end-to-end compliance process, identify friction points affecting efficiency and accuracy, and propose process-based recommendations to enhance digital tax performance. Using a qualitative case study approach, data were collected through process documentation, system audit, and regulatory review. Analytical techniques such as service blueprinting, friction metrics, and compliance funnel analysis were employed to locate inefficiencies in user interaction, system integration, and data validation. The findings reveal that major frictions arise from duplicated document verification, asynchronous system interfaces, and inconsistent regulatory standards. Barokah Travel mitigates these issues through integrated financial systems, reconciled transaction reporting, and adaptive tax planning across jurisdictions. The study concludes that simplifying digital tax workflows and enhancing UX-driven process design improve compliance outcomes and support inclusive, transparent, and innovative governance, aligning with SDG 9 and SDG 16.